Gender bias and menstrual blood in stem cell research: A review of pubmed articles (2008–2020) - Manica, Daniela Tonelli; Asensi, Karina Dutra; Mazzarelli, Gaia; Tura, Bernardo; Barata, Germana; Goldenberg, Regina Coeli Santos (Frontiers in Genetics, 2022)
Despite proven scientific quality of menstrual blood mesenchymal cells, research and science output using those cells is still incipient, which suggests there is a resistance to the study of this type of cell by scientists, and a lack of attention to its potential to cell therapy, regenerative medicine and bioengineering.. This study analyzes the literature of the menstrual blood mesenchymal stromal/stem cells (mbMSC) at PubMed database between 2008 – 2020 and the social attention it received on Twitter. A comparative analysis showed that mbMSC has a very small space within mesenchymal cells research (0.25%). Most first authors are women (53.2%), whereas most last authors are men (63.74%), reinforcing an already known, and still significant, gender gap between last and corresponding authors. Menstrual blood tends to be less used in experiments and its scientific value tends to be underestimated, which brings gender bias to a technical and molecular level. Although women are more positive in the mbMSC debate on Twitter, communication efforts toward visibility and public interest in menstrual cells has room to grow.